High environmental temperature and low pH stress alter the gill phenotypic plasticity of Hoven’s carp Leptobarbus hoevenii - Suhaini Mohamad; Hon Jung Liew; Rabiatul Adawiyyah Zainuddin; Sharifah Rahmah; Khor Waiho; Mazlan Abd Ghaffar; Hua Tha Nhan; Jiun-Yan Loh; Lim, Leong Seng; Yumei Chang; Liqun Lian; De Boeck, Gudrun (John Wiley and Sons Inc, 2021)
Climate warming and low pH environment are known to negatively impact all levels of aquatic organism from cellular to organism and population levels. For ammonotelic freshwater species, any abiotic factor fluctuation will cause disturbance to the fish, specifically at the gills which act as a multifunctional organ to support all biological processes. Therefore, this study was designed to investigate the effect of temperature (28 vs. 32°C) and pH (7.0 vs. 5.0) stress on the gill plasticity of Hoven's carp after 20 days of continuous exposure. The results demonstrated that high temperature and low pH caused severe changes on the primary and secondary lamellae as well as the cells within lamellae. An increasing trend of the proportion available for gas exchange was noticed at high temperature in both pH exposures, which resulted from a reduction of the primary lamellae width with elongated and thinner secondary lamellae compared to fishes at ambient temperature. Following exposure to high temperature and acidic pH, Hoven's carp experienced gill modifications including aneurysm, oedema, hypertrophy, curling of secondary lamellae, epithelial lifting, hyperplasia and lamellae fusion. These modifications are indicators of the coping mechanism of Hoven's carp to the changing environment in order to survive.